Analysis of the Influence of Nutrition Education on Nutritional Knowledge of Basketball Athletes in Medan - Harahap, Nur Kholilah; Nabila, Miftahul; Ramadhana, Anyelir Teta (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
Knowledge about proper nutrition is very important to support athlete performance, especially in improving endurance, recovery, and physical performance. This study aims to analyze the effect of nutrition education on nutritional knowledge in adolescent basketball athletes in Medan. This study uses a qualitative approach with observation and literature study related to the nutrition education program followed by adolescent basketball athletes. The data obtained were analyzed thematically to identify changes in athletes' understanding of the importance of proper nutritional intake. The results of the study indicate that nutrition education can improve athletes' understanding of the role of carbohydrates, proteins, and fats in supporting their sports performance. In addition, the nutrition education program also plays a role in changing athletes' eating habits by encouraging them to consume more nutritious foods that are in accordance with their body's needs. The support factor of coaches and families and the sustainability of the nutrition education program are important aspects in the application of this nutritional knowledge. This study suggests that nutrition education should be an integral part of adolescent basketball athlete training to maximize their performance and health.